2020
DOI: 10.1093/jac/dkz527
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of honey in periodontal disease: a systematic review

Abstract: Background Honey has shown positive antimicrobial and anti-inflammatory actions in several dermatological studies; however, it is unclear if it could be effective in the treatment of periodontal disease. Objectives To answer the question: Does honey have antimicrobial activity against periodontopathogens? Methods Six electronic databases were screened from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…There are many studies in the literature on the usefulness of honey in the prevention and treatment of OM based on the biological properties of this agent. As an anti-inflammatory and antimicrobial agent and immunomodulator, this natural product has a great impact on OM [8][9][10][11]13,51,52]. For example, Pradip Kumar Maiti et al conducted a study on 50 patients diagnosed with head and neck cancer who were radiotreated and divided into two study groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many studies in the literature on the usefulness of honey in the prevention and treatment of OM based on the biological properties of this agent. As an anti-inflammatory and antimicrobial agent and immunomodulator, this natural product has a great impact on OM [8][9][10][11]13,51,52]. For example, Pradip Kumar Maiti et al conducted a study on 50 patients diagnosed with head and neck cancer who were radiotreated and divided into two study groups.…”
Section: Discussionmentioning
confidence: 99%
“…The management of oncological toxicities is a challenge for clinicians today, especially concerning the education of patients in regards to the oral hygiene, diet, and lifestyle changes, as well as the management of pain according to intensity, symptoms, prevention of complications, prophylaxis, or treatment of secondary infections [26]. A crucial aspect is an early diagnosis and appropriate treatment of dental diseases [9,35].…”
Section: Management Of Ommentioning
confidence: 99%
See 1 more Smart Citation
“…Natural products attract more and more attention in periodontitis treatment due to their therapeutic potential, cost-effectiveness, enough source, and safety. A series of natural products such as honey, propolis, cannabidiol, and green tea show various benefits in periodontitis treatment and prevention including inhibition of periodontal pathogens, anti-inflammation, immunomodulation, and osteogenesis (76)(77)(78)(79)(80)(81)(82)(83)(84)(85). But the low stability, uncertain bioavailability, and limited therapeutic effect of natural products limit their clinical application.…”
Section: Treatment Of Periodontitismentioning
confidence: 99%
“…Concerning the included in vitro studies, the risk of bias assessment was based on and adapted from the judgement model suggested by previous systematic reviews [34][35][36] for the assessment of risk of bias in in vitro trials. Therefore, the following eight domains were considered: quality check of samples; randomization of samples; sample-size calculation; homogeneity of samples; details of laser parameters used; fluoride application protocol; operator training; and blinding of operator.…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 99%